Peluang dan Tantangan Bank Syariah di Masa Pandemi Covid 19 - Hardiansyah Padli; Kumaidi , (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
ABSTRACT The COVID-19 pandemic has had a major impact on the economy, and the banking sector is no exception. What is quite different can be seen that the growth of Islamic banks shows a positive trend. This article was compiled to analyze the opportunities and challenges faced by Islamic banks during the Covid 19 pandemic. This article uses qualitative data analysis with descriptive-critical methods and through a literature study approach. The data analysis focuses on the opportunities and challenges of Islamic banks during the Covid 19 pandemic. Researchers used secondary data as a source of article creation. Based on the results of the study, it was revealed that Islamic banks have opportunities in the form of: historically and the application of profit-sharing contracts makes Islamic banks more crisis-resistant, Indonesia is the country with the largest Muslim population, the pandemic has made businesses digitize this as a market share for Islamic banks. Meanwhile, the challenges faced by Islamic banks are financing risks due to unstable market conditions, the imposition of restrictions on human mobility and limited capital investment for technology improvement.